The Influence of Experiential Learning on Self-Confidence, Communication, Human Relations and Leadership in the State Civil Apparatus in Indonesia - ., Wangsih; Madjid, Udaya; ., Busiri; Alyani, Neni; Alfian, Yani (Journal of Ecohumanism, 2024)
The challenge to show the quality of life in shaping character is getting higher, although the results of the last 21 years of research on the development of character quality are more researched on academic variables, but the last three years have focused more on the learning process and on the research method side is still oriented to correlational studies, so that the research objectives will construct the effect of experiential learning (MPE) for the development of character quality (Self Confidence, Communication, Human Relations and Leadership) with Mixed Methodology methods through Concurrent Embedded Design and research samples conducted in the State Civil Apparatus (ASN) environment as many as 10 people who served as employees in Indonesia were randomly selected. MPE intervention was given to the experimental group for 6 months. Quantitative data analysis techniques with Trace, Wilks' Lambda, Hotelling's Trace and Roy's Largest Root techniques, while qualitative data analysis techniques obtained from questionnaires, interviews, observations using the NVivo application by making nodes and coding. The results of the research on the components of self-confidence, communication and leadership are the largest in the group given debriefing.